2005
DOI: 10.1536/ihj.46.205
|View full text |Cite
|
Sign up to set email alerts
|

Are the High Levels of Cytomegalovirus Antibodies a Determinant in the Development of Coronary Artery Disease?

Abstract: SUMMARYIn several epidemiological studies, it was suggested that a high titer of cytomegalovirus (CMV) antibody meant CMV reactivation, and that this condition was a determinant of coronary artery disease (CAD). The purpose of this study was to investigate both the prevalence of the CMV infections in our study population and whether high CMV seropositivity is a determinant of CAD. Blood samples from 179 (58 female, 121 male) individuals being evaluated for CAD suspicion by coronary angiography were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
0
10
1
1
Order By: Relevance
“…One possibility is that reduced cellular immunity associated with symptoms of depression compromises the immune system's ability to resist infection. This may allow chronic and latent infections to be activated and replicate within the body (e.g., periodontal disease, Chlamydia pneumoniae, and herpes virus infection) leading to inflammatory host responses to pathogens (41)(42)(43). Unexpectedly, the present study did not find a corresponding increase in the inflammatory marker IL-6 in association with Hamilton Depression Scores, cardiac morbidity, or a reduction of Th1/Th2 ratios.…”
Section: Discussioncontrasting
confidence: 63%
“…One possibility is that reduced cellular immunity associated with symptoms of depression compromises the immune system's ability to resist infection. This may allow chronic and latent infections to be activated and replicate within the body (e.g., periodontal disease, Chlamydia pneumoniae, and herpes virus infection) leading to inflammatory host responses to pathogens (41)(42)(43). Unexpectedly, the present study did not find a corresponding increase in the inflammatory marker IL-6 in association with Hamilton Depression Scores, cardiac morbidity, or a reduction of Th1/Th2 ratios.…”
Section: Discussioncontrasting
confidence: 63%
“…However, the available data are not entirely consistent. Some studies showed a significant association between CMV infection and atherosclerosis/CAD (3,(5)(6)(7)(8)(9)(10), while some others did not (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Ji et al conducted an aggregate data metaanalysis involving 9,000 patients with CAD and 8,608 controls from a total of 55 studies, and concluded that CMV infection was associated with an increased risk of CAD (24).…”
Section: Cytomegalovirus Infection and Coronary Artery Disease: A Sinmentioning
confidence: 99%
“…It could be associated with persistent, latent, and recurrent infections. Besides, it has been shown that the reactivations of the latent virus could happen in the vascular wall cells (3).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, evidence has emerged of a link between HCMV and restenosis, primary atherosclerosis, and posttransplant arteriosclerosis (13)(14)(15)(16), and animal experiments (17)(18)(19)(20)(21)(22) have supported the documented clinical associations (23)(24)(25)(26)(27)(28)(29). Among these findings is the observation by Streblow et al (30) demonstrating that expression of the HCMV-encoded CC chemokine receptor, US28, in the presence of MCP-1 or RANTES, has the potential to exacerbate atherosclerosis by inducing smooth muscle cell migration.…”
Section: H Uman Cytomegalovirus (Hcmv)mentioning
confidence: 99%